Recent Research Developments Affecting Nonlife Insurance—The CAS Risk Premium Project 2014 Update. Issue 1 (March 2017) - Eling, Martin; Jia, Ruo
Abstract: This article discusses the main results of the Casualty Actuarial Society Risk Premium Project 2014 update. It reviews the recent research developments in the process of nonlife risk assessment. Of special note, systemic risk continuously attracts a great deal of attention. In the past year, reinsurance studies have increased significantly, driven by progress in optimal reinsurance design and reinsurance asymmetric information. Both topics show the academic reflection of financial crisis in the field of risk and insurance. The evaluation of reserves and the methods mitigating asymmetric information have also received a great deal of attention.